2017
DOI: 10.1111/imm.12811
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of tolerogenic dendritic cells towards heat‐shock proteins: a novel therapeutic strategy for autoimmune diseases?

Abstract: SummaryTolerogenic dendritic cells (tolDCs) are a promising therapeutic tool to restore immune tolerance in autoimmune diseases. The rationale of using tolDCs is that they can specifically target the pathogenic T-cell response while leaving other, protective, T-cell responses intact. Several ways of generating therapeutic tolDCs have been described, but whether these tolDCs should be loaded with autoantigen(s), and if so, with which autoantigen(s), remains unclear. Autoimmune diseases, such as rheumatoid arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 95 publications
(182 reference statements)
0
14
0
Order By: Relevance
“…The challenge of Treg therapy is how to achieve the expansion of antigen-specific Tregs and how to determine the appropriate antigen(s) to activate the Tregs. One remarkable strategy that is developing is using tolerogenic dendritic cells to induce Tregs that are active against heat-shock proteins (HSPs) ubiquitously expressed in inflamed target tissues [119].…”
Section: Part Ii: Current Immune Target Therapy and On-going Immunmentioning
confidence: 99%
“…The challenge of Treg therapy is how to achieve the expansion of antigen-specific Tregs and how to determine the appropriate antigen(s) to activate the Tregs. One remarkable strategy that is developing is using tolerogenic dendritic cells to induce Tregs that are active against heat-shock proteins (HSPs) ubiquitously expressed in inflamed target tissues [119].…”
Section: Part Ii: Current Immune Target Therapy and On-going Immunmentioning
confidence: 99%
“…However, CIA mice receiving the transfer of STAT3ca-transduced DCs displayed a significantly stronger reduction of CIA manifestation in comparison with those mice receiving DCs treated with vitamin D3 (data not shown). Although a number of studies have shown that tolerogenic DCs need to be pulsed with a disease-relevant autoantigen to induce an anti-inflammatory effect in autoimmune disorders, another group of studies has suggested that nonloaded tolerogenic DCs might take up relevant autoantigens in vivo and exert a therapeutic effect dampening inflammation [50, 51]. Thereby, whether the loading of tolerogenic DCs with autoantigens is necessary or not to attenuate inflammation in autoimmune disorders remains controversial.…”
Section: Resultsmentioning
confidence: 99%
“…We are planning now a phase I-II, unblinded, longitudinal study with RA patients in remission or with low disease activity under conventional therapy. 33 In our case the dexamethasone and Vit D3 tolerized DC will be loaded with a well-characterized HSP70 derived peptide, which is called HSP70-B29. 34 Peptide HSP70-B29 is conserved, and T cells were shown to cross-respond between the microbial and the self-peptide both in mice and in humans.…”
Section: Therapeutic Tolerancementioning
confidence: 99%